2015
DOI: 10.1111/josh.12342
|View full text |Cite
|
Sign up to set email alerts
|

Twelve‐Month Effects of the COPE Healthy Lifestyles TEEN Program on Overweight and Depressive Symptoms in High School Adolescents

Abstract: BACKGROUND We evaluated the 12-month effects of the COPE (Creating Opportunities for Personal Empowerment) Healthy Lifestyles TEEN (Thinking, Emotions, Exercise, Nutrition) program versus an attention control program (Healthy Teens) on overweight/obesity and depressive symptoms in high school adolescents. METHODS A cluster randomized controlled trial was conducted. Participants were 779 culturally diverse adolescents in the US Southwest. COPE is a cognitive-behavioral skills-building intervention with 20 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
86
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(88 citation statements)
references
References 35 publications
0
86
0
2
Order By: Relevance
“…Management or frequency of symptoms was examined in 44 studies. Four of the studies that had investigated symptom frequency found no differences, and 25 studies reported reduction of symptoms and/or awareness of symptom triggers . Ten studies from interventions tailored to children and adolescents with asthma reported improved asthma control and decreased number of asthma exacerbations.…”
Section: Resultsmentioning
confidence: 97%
“…Management or frequency of symptoms was examined in 44 studies. Four of the studies that had investigated symptom frequency found no differences, and 25 studies reported reduction of symptoms and/or awareness of symptom triggers . Ten studies from interventions tailored to children and adolescents with asthma reported improved asthma control and decreased number of asthma exacerbations.…”
Section: Resultsmentioning
confidence: 97%
“…self-reported or parent-reported questionnaires) (Gee 2014; Goldfield 2012; Muzaffar 2014; Naar-King 2016; Pentz 2011; Salmoirago-Blotcher 2015; Smith 2015; Wong 2016). …”
Section: Resultsmentioning
confidence: 99%
“…The HLBS has construct validity and Cronbach alphas reported at ≥ 0.80. 24 Secondary outcomes included depressive and anxiety symptoms, social skills, substance use, and academic performance. (i.e., grade in the health course).…”
Section: Methodsmentioning
confidence: 99%